Evaluation of a simulation-based hospital pharmacy training package for pharmacy students - Hattingh, H. Laetitia; Robinson, Denise; Kelly, A. (2018)
© 2018, The Author(s). This study describes the process undertaken to develop, implement and evaluate a simulation-based training package focused on medication management and reconciliation processes for final year pharmacy students about a patient’s hospital journey. A five module training package was developed following a literature review and consultation with stakeholders. The simulation-based package immersed students in a real-life scenario and was delivered to final year pharmacy students over a six-week period in 2016. Data on knowledge, skills and confidence was collected via a survey in the week preceding engagement with the online training package and 1 week post completion of the training. The mean score was compared across four student categories: three categories incorporated students who had not completed a hospital pharmacy placement and one category comprised students who had completed a hospital placement. Qualitative feedback was collected via an online survey at the conclusion of the training program. Of the 79 participants, 44 (55.7%) completed both the pre and post- test surveys that showed the change in score was statistically significant. There was a significant positive change in mean test scores across all four student categories for the domains of skills, knowledge and confidence. Assessment of students’ confidence according to 16 ranking statements also improved markedly post-training. Thirty-one students provided qualitative feedback that was generally positive. The positive outcomes reinforce the rationale to include online simulation-based methodologies as part of pharmacy education programs. The model provides a reproducible framework for online simulated learning activities that could be applied within various professions and educational environments.